2014
DOI: 10.1586/14760584.2014.990387
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of climate change and ultraviolet radiation on vaccine-preventable infectious diseases and immunization service delivery system

Abstract: Climate change and solar ultraviolet radiation may affect vaccine-preventable infectious diseases (VPID), the human immune response process and the immunization service delivery system. We systematically reviewed the scientific literature and identified 37 relevant publications. Our study shows that climate variability and ultraviolet radiation may potentially affect VPID and the immunization delivery system through modulating vector reproduction and vaccination effectiveness, possibly influencing human immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 85 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…A study in Hong Kong found solar radiation was positively associated with all respiratory disease hospitalizations [ 39 ]. Some vaccine-preventable infectious diseases, including Japanese encephalitis, yellow fever, influenza, rotavirus infection, hepatitis A virus infection and hepatitis B virus infection, were also found to be differentially influenced by ultraviolet radiation from the sun through modulating vector reproduction [ 40 ]. In addition, a preventive effect of indoor solar radiation on HFMD was presumed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Hong Kong found solar radiation was positively associated with all respiratory disease hospitalizations [ 39 ]. Some vaccine-preventable infectious diseases, including Japanese encephalitis, yellow fever, influenza, rotavirus infection, hepatitis A virus infection and hepatitis B virus infection, were also found to be differentially influenced by ultraviolet radiation from the sun through modulating vector reproduction [ 40 ]. In addition, a preventive effect of indoor solar radiation on HFMD was presumed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies indicate that UVR-induced immune suppression is both local and systemic and may affect delayed type hypersensitivity reactions. Exposure to SR may reactivate latent viral infections (e.g., herpes simplex virus) and epidemiological studies suggest that SR exposure may impair to some extent the effectiveness of vaccines [72][73][74]. As shown in Figure 1, several potential implications of SR-induced immune suppression (some of them involving a net beneficial effect while others result in adverse outcomes) are not yet clearly highlighted by experimental and epidemiological studies.…”
Section: Immune Effectsmentioning
confidence: 99%
“…Sunlight may increase temperatures at the ground level, particularly in concrete‐dominated urban settings, contributing to viral spread . Moreover, certain vaccine‐preventable infections have been found to be differentially influenced by ultraviolet radiation via modulation of vector reproduction, suggesting that sunlight may play a role in disease transmissibility . In theory, stronger winds may facilitate the spread of respiratory droplets up to a certain threshold, after which extreme wind speeds may hinder attachment to materials in the environment …”
Section: Discussionmentioning
confidence: 99%